Special features of the web-textbook of Vocational Education - Huraliuk, Andriy (Professional Pedagogics, 2015)
Modern education is focused on the use of various forms and methods of an educational process organization. One of the most actual and promising areas of modern pedagogy is the use of electronic manuals and textbooks. The Laboratory for electronic educational resources has theoretically proved and developed a methodology of electronic textbooks creation and application in educational process of vocational schools. It has also elaborated a technology of creation and use of web-textbooks as electronic textbooks of a new generation. On the basis of numerous researches and their practical implementation a (www.profua.info) content library of electronic textbooks on vocational education majors and a range of individual platforms for developing and placing the electronic textbooks of a new generation in the Internet were created. The article describes some special features of technological solutions: distributed locations of web- resources, increase of data processing speed at a server. The opportunity to use third-party depositories in order to reduce the load on a single server platform manual is proved. Particular issues related to copyright etc. are solved. Construction of the main resource (integration system) based on CMS Joomla 2.5 allows to use all peculiarities of this system, namely: flexible tools for account management interface, media files management interface, service for creation of multilingual versions of pages, user’s address book, voting, categorizing links and functions of accounting clicks, system templates, menu support, news flow control, XML-RPC API for integration with other systems, cashing pages support, and a large set of ready add-ins. One of these additions is used in the platform WYSIWYG-editor JCE which is one of the best WYSIWYG editors in its class at the moment. Besides, CMS Joomla 2.5 allows to easily use third-party technologies. So, the general search of resources in the content library is implemented using a custom search on ...